2020
DOI: 10.1038/s41467-020-17271-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the DOCK2−ELMO1 complex provides insights into regulation of the auto-inhibited state

Abstract: DOCK (dedicator of cytokinesis) proteins are multidomain guanine nucleotide exchange factors (GEFs) for RHO GTPases that regulate intracellular actin dynamics. DOCK proteins share catalytic (DOCK DHR2 ) and membrane-associated (DOCK DHR1 ) domains. The structurally-related DOCK1 and DOCK2 GEFs are specific for RAC, and require ELMO (engulfment and cell motility) proteins for function. The N-terminal RAS-binding domain (RBD) of ELMO (ELMO RBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 76 publications
12
86
0
1
Order By: Relevance
“…18 Likewise, FE65 binds ELMO1/DOCK1/2 to stimulate ELMO1 by disrupting its autoinhibitory closed conformation 7 and consequently releasing DOCK1/2 from its autoinhibition. 45 The ARF6-FE65-ELMO1/ DOCK1/2 complex is then trafficked through the endosomal recycling pathway to the PM to induce Rac1 activation and consequently neurite outgrowth In conclusion, we demonstrate that FE65 orchestrates ARF6 and ELMO1 to form a tripartite signaling complex and stimulate neurite outgrowth by promoting the PM trafficking of ELMO1 through the ARF6-regulated endosomal recycling pathway ( Figure 6).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…18 Likewise, FE65 binds ELMO1/DOCK1/2 to stimulate ELMO1 by disrupting its autoinhibitory closed conformation 7 and consequently releasing DOCK1/2 from its autoinhibition. 45 The ARF6-FE65-ELMO1/ DOCK1/2 complex is then trafficked through the endosomal recycling pathway to the PM to induce Rac1 activation and consequently neurite outgrowth In conclusion, we demonstrate that FE65 orchestrates ARF6 and ELMO1 to form a tripartite signaling complex and stimulate neurite outgrowth by promoting the PM trafficking of ELMO1 through the ARF6-regulated endosomal recycling pathway ( Figure 6).…”
Section: Discussionmentioning
confidence: 67%
“…Recently, it has been shown that conformational change of ELMO1 is required for the release of the autoinhibitory conformation of the ELMO1-DOCK bipartite Rac1 GEF complex. 45 Intriguing, an interaction of FE65 and ELMO1 has been shown to promote the relieve of the closed conformation F I G U R E 3 ARF6-FE65-ELMO1 interaction potentiates neurite outgrowth. (A, B, C, D, and E) Rat embryonic E18 cortical neurons were isolated and transfected with EGFP as a cell morphology marker, together with different combinations of plasmid DNAs and/or siRNAs as indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GTP-loaded Cdc42 and PI(4,5)P2 serve as the coincidence detection signals for activation of Wiskott-Aldrich syndrome protein, which stimulates Arp2/3 complex–mediated actin polymerization for reorganization of the actin cytoskeleton. In a similar, but distinct way, the DOCK-A subfamily member (e.g., DOCK2), which makes a signaling complex with engulfment and cell motility (ELMO) protein through the SH3 domain ( Hanawa-Suetsugu et al, 2012 ; Chang et al, 2020 ), is recruited to the leading edge of migrating cells through the PI(3,4,5)P3–binding DHR-1 domain in response to chemoattractant signals. The DHR-2 domain of the DOCK-A subfamily activates Rac, which in turn acts in synergy with PI(3,4,5)P3 to activate WAVE complex.…”
Section: Discussionmentioning
confidence: 99%